MODEL PEMBELAJARAN KEAKSARAAN DASAR MENGGUNAKAN KOMBINASI METODE REFLECT, LEA, DAN PRA - Sumardi, Kamin (JIV-Jurnal Ilmiah Visi, 2008)
This study aimed at producing an effective functional literacy learning model by combining three methods, which are Regenerated Frerian Literacy through Empowering Community Techniques (REFLECT), Language Experience Approach (LEA) and Participatory Rural Appraisal (PRA). This study applied qualitative approach and employed research and development as the methods. The study concludes that literacy learning model using REFLECT, PRA and LEA is effective in learning reading, writing and numerical problems.